PENGUKURAN TINGKAH LAKU PADA MODEL NYERI NEUROPATIK PERIFER: TIKUS DENGAN CCI (CHRONIC CONSTRICTION INJURY) - Hanik Badriyah Hidayati; Paulus Sugianto; Junaidi Khotib; Chrismawan Ardianto; Kuntoro Kuntoro; Mohammad Hasan Machfoed (NEURONA, 2018)
BEHAVIORAL ASSESMENT OF THE PERIPHERAL NEUROPATHIC PAIN MODEL: RAT WITH CCI (CHRONIC CONSTRICTION INJURY)ABSTRACTNeuropathic pain occurs in 20% of patients with chronic pain. This mainly due to the lack of effective treatment and the presence of drug’s side effects. Animal models have been broadly utilized in validating the therapeutic target and the development of analgesic drugs. Chronic constriction injury (CCI) is a model of peripheral neuropathic pain characterized by allodynia and hyperalgesia. Chronic constriction injury model is produced by loose ligation of the sciatic nerve resulting in nerve damage, thus sensitizes and lowers pain threshold. The pain threshold test is performed by providing a pressure and thermal sensory stimulus that results in observable withdrawal behavior. This article discusses several methods in assessing pain-related behavior on the CCI neuropathic pain model.Keywords: Behavioral, chronic constriction injury, mechanical, neuropathic painABSTRAKNyeri neuropatik terjadi pada seperlima pasien dengan nyeri kronik. Hal ini disebabkan karena terapi nyeri neuropatik masih kurang efektif dan adanya efek samping obat. Model hewan terbukti bermanfaat untuk validasi target dan perkembangan obat analgesik. Chronic constriction injury (CCI) merupakan model nyeri neuropatik perifer dengan karakteristik alodinia dan hiperalgesia. Model CCI dibuat dengan memberikan ligasi longgar pada saraf skiatik yang menyebabkan kerusakan saraf, sehingga terjadi sensitisasi dan ambang nyeri menurun. Tes ambang nyeri dilakukan dengan memberikan stimulus sensorik berupa tekanan dan panas yang akan menghasilkan tingkah laku withdrawal yang bisa diobservasi. Artikel ini membahas penilaian tingkah laku nyeri pada model nyeri neuropatik CCI.Kata kunci: Chronic constriction injury, mekanik, nyeri neuropatik, tingkah laku